NINAABINOOTAAN OWE DIBAAJIMOWIN: I’m passing on this story - Banaishe Kicknosway, Misko (Scholarship@Western, 2022)
This research project begins from an understanding that Indigenous knowledge is a practice, as Deborah McGregor describes-what one does. Using this description as a starting place, we will explore the “doing” or the practice of traditional Indigenous research, through three interconnected Indigenous practices: storytelling, mark making and participating in ceremonies. Exploring the interconnections between these practices and how knowledge is braided together through participation in these Indigenous ways of coming to know. This is for the future generations to come.